Copper‐Mediated Remote Highly Site‐Selective C–H Bond Bromination and Chlorination of Quinolines at the C5 Position that is Geometrically Difficult to Access. Issue 3 (20th December 2016) - Rao, Naidu Sambasiva; Reddy, Ganapam Manohar; Sridhar, B.; Sarma, Maheswaran Harihara
Abstract : A concise, simple, and efficient method for remote C–H bond halogenation (Br and Cl) of 8‐aminoquinoline scaffolds at the geometrically difficult‐to‐access C5 position was explored with diverse substrate combinations in DMF. This protocol made use of inexpensive CuBr2 and CuCl2 as mediators and showed good to excellent yields for as many as 24 substrate combinations. The outstanding site selectivity of the reaction was reflected by the lack of formation of the undesired C7‐halogenated byproduct originating from the high nucleophilic reactivity of the 8‐aminoquinoline scaffold at the C7 position, even if excess amounts of the CuX2 salts were used. Abstract : A concise and efficient method for remote C–H bond halogenation (Br and Cl) of 8‐aminoquinoline scaffolds at the geometrically difficult‐to‐access C5 position is reported. The protocol makes use of inexpensive CuBr2 and CuCl2 as mediators and shows good tolerance toward numerous N ‐(8‐quinolinyl)benzamides to give the corresponding products in good to excellent yields.